Determinação da frequência de características morfológicas em uma amostra de crianças com desenvolvimento típico: um estudo transversal - Perrone, Eduardo [UNIFESP] (2016)
Purpose: to establish the frequency of 82 morphological features in a sample of Brazilian children (between 3 and 13 years old), to compare with literature data and to understand the age and gender influence in this frequency. Methods: our study is a cross sectional study. We evaluated 239 typical developed children (between 3 and 13 years old) regarding the presence of 82 morphological features. We applied a previous described protocol, based on London Dysmorphology Database, to evaluate our sample. This protocol was culturally adapted to Brazilian Portuguese. Results: the frequency of 82 morphological features was established in our sample; from 82 features, 50% were considered morphological anomalies (frequency less than 4%). At least 25% of our sample had more than one minor morphological anomalies. Age showed influence in frequency of the following morphological features: ?widow´s peak?, ?prominent anti-helix?, ?prominent upper lip? ?irregular or crowded teeth? and ?clinodactyly?, but had no influence in frequency of minor morphological anomalies. Gender showed influence in the following features ?dysplastic ears? and ?attached ear lobe?, but had no influence in frequency of minor morphological anomalies. There was divergence (statistically significant) in 43 morphological features from 73 that we could compare with literature data (58,9%). Conclusions: We established the frequency of 82 morphological features in 239 typical developed children. Age was the variable that showed more influence in frequency of morphological features and comparison with literature data showed that the frequency depends on variables like age and race.